Linear Artificial Muscle Based on Ionic Electroactive Polymer: A Rational Design for Open‐Air and Vacuum Actuation. Issue 2 (7th December 2018) - Fannir, Adelyne; Temmer, Rauno; Nguyen, Giao T. M.; Cadiergues, Laurent; Laurent, Elisabeth; Madden, John D. W.; Vidal, Frederic; Plesse, Cedric
Abstract: The development of linear muscle‐like actuators remains a key objective in the field of electroactive polymers (EAPs). While ionic EAPs are promising technologies to develop biomimetic artificial muscles, their reliance on liquid electrolytes for operation typically restricts them to use in bending devices. Seldom have ionic linear actuators been demonstrated in air, and never in vacuum. Here both are demonstrated. A rational approach supported by a theoretical model is described to identify the general conditions allowing the design of ionic actuators with intrinsically linear deformations. The model highlights that linear deformation can occur by combining two electroactive electrodes with different mechanical and/or electromechanical properties. Where previous work on laminated actuators resulted in bending only, here it is shown that by combining one soft and one stiff electrode, or one highly expanding electrode, and the other minimally deforming electrode, 0.55% linear strain is achieved when activated with 2 V. Best combination of electrodes is selected based on electromechanical model predictions. Single actuator fibers are fabricated for experimental validation. Graded force up to 0.18 N has been achieved by bundling together five linear actuators. The resulting artificial muscles operate in open‐air, and also under high vacuum conditions, opening possibilities for space applications. Abstract : A linear polymer actuator operating in air and in vacuum mimics muscle in its ability to scale forces using recruitment of parallel fibers . In this new approach, a rational design of linear artificial muscles supported by electromechanical model is described for ionic electroactive polymers. Artificial muscle bundles are developed and operated in open‐air but also under high vacuum conditions.